2006
DOI: 10.1080/00268970601005235
|View full text |Cite
|
Sign up to set email alerts
|

On the calculation of the spectrum of large Hückel matrices, representing carbon nanotubes, using fast Hadamard and symplectic transforms

Abstract: To cite this article: J. R. Alvarez Collado (2006) On the calculation of the spectrum of large Hückel matrices, representing carbon nanotubes, using fast Hadamard and symplectic transforms, Molecular Physics,The Hu¨ckel theory is reviewed and improved. The usefulness of several Hadamard fast transforms when preconditioning binary Hu¨ckel matrices is compared and analysed. The spectrum of large benchmark (circulant) matrices is obtained by combining the SylvesterHadamard transform, the Singular Value Decomposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…The Hückel spectra of two non-helical (zigzag) nanotubes, having 2 ny cycles of length 2 nx atoms, were presented in the previous paper. 15 These results have been ratified by the present code to be much more reliable, since the correct behavior of the several kinds of eigenvector have been checked by suitable subroutines. Two recent works, 33,34 which have been found by using the Google searching engine, 35 confirm the fine structure of the density of states, for infinite (cyclic) nanotubes.…”
Section: Analysis Of Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…The Hückel spectra of two non-helical (zigzag) nanotubes, having 2 ny cycles of length 2 nx atoms, were presented in the previous paper. 15 These results have been ratified by the present code to be much more reliable, since the correct behavior of the several kinds of eigenvector have been checked by suitable subroutines. Two recent works, 33,34 which have been found by using the Google searching engine, 35 confirm the fine structure of the density of states, for infinite (cyclic) nanotubes.…”
Section: Analysis Of Resultssupporting
confidence: 54%
“…10 Some of these papers describe, on a theoretical basis, how electronic structure depends on the length of the tube itself. [11][12][13][14] The present study is a continuation of a previous paper, 15 where large finite length (N ≈ 16.000) nanotubes were studied. The spectra of their Hückel matrices was obtained by applying SVD Hadamard-Symplectic transforms on them.…”
Section: Introductionmentioning
confidence: 78%
“…The PPP-weighted graphs are expected to grow rapidly in size as a function of tessellation parameters. Even for very large tessellations, it has been shown that Hadamard-transform-based orthogonal matrices provide all the eigenvalues and eigenvectors quite efficiently as shown in previous works. Consequently, graph-theory-based PPP techniques offer a viable alternative for energy computations of large tessellations of kekulenes with ab initio -derived parameters compared to DFT or other techniques, as the graph-theory-based PPP method focuses on π electrons of these systems. Moreover, computations of TREs of larger tessellations appear to be intractable due to combinatorial explosions in the coefficients of their matching polynomials.…”
Section: Results and Discussionmentioning
confidence: 90%
“…The subject matters of hypercubes, polycubes and wreath product groups have been dealt with by several researchers over the years , including techniques to obtain topological Symmetry 2023, 15, 557 2 of 20 indices [41][42][43][44][45][46][47][48][49][50] by cut methods which involve subgraphs of hypercubes [41,42]. Furthermore, graph spectra, matching polynomials, distance degree sequences, topological indices and other properties of graphs pertinent to chemical applications have been the subject matter of several studies [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67].…”
Section: Introductionmentioning
confidence: 99%